Self-monitoring of Blood Glucose in Non-Insulin Treated Type 2 Diabetes (The SMBG Study): study protocol for a randomised controlled trial. Issue 1 (December 2017) - Parsons, Sharon; Luzio, Stephen; Bain, Stephen; Harvey, John; McKenna, Jillian; Khan, Atir; Rice, Sam; Watkins, Alan; Owens, David
Abstract Background The benefit of Self-monitoring of Blood Glucose (SMBG) in people with non-insulin treated type 2 diabetes remains unclear with inconsistent evidence from randomised controlled trials fuelling the continued debate. Lack of a consistent finding has been attributed to variations in study population and design, including the SMBG intervention. There is a growing consensus that structured SMBG, whereby the person with diabetes and health care provider are educated to detect patterns of glycaemic abnormality and take appropriate action according to the blood glucose profiles, can prove beneficial in terms of lowering HbA1c and improving overall well-being. Despite this, many national health agencies continue to issue guidelines restricting the use of SMBG in non-insulin treated type 2 diabetes. Methods The SMBG Study is a 12 month, multi-centre, randomised controlled trial in people with type 2 diabetes not on insulin therapy who have poor glycaemic control (HbA1c ≥58 mmol/mol / 7.5%). The participants will be randomised into three comparative groups: Group 1 will act as a control group and receive their usual diabetes care; Group 2 will undertake structured SMBG with clinical review every 3 months; Group 3 will undertake structured SMBG with additional monthly telecare support from a trained study nurse. A total of 450 participants will be recruited from 16 primary and secondary care sites across Wales and England. The primary outcome measure will be HbA1c at 12 months with secondary measures to include weight, BMI, total cholesterol and HbA1c levels at 3, 6, 9 and 12 months. Participant well-being and attitude towards SMBG will be monitored throughout the course of the study. Recruitment began in December 2012 with the last participant visit due in September 2016. Discussion This study will attempt to answer the question of whether structured SMBG provides any benefits to people with poorly controlled type 2 diabetes who are not being treated with insulin. The data will also clarify whether the telecare support provides additional value. The overall acceptability of SMBG as a tool for self-management will be assessed. Trial registration UKCRN 12038 (Registered March 2012). ISRCTN21390608 (Retrospectively registered 15th May 2014).